Racial/ethnic differences in pediatric asthma management: the importance of asthma knowledge, symptom assessment, and family-provider collaboration. (3rd October 2021) - Tackett, Alayna P.; Farrow, Michael; Kopel, Sheryl J.; Coutinho, Maria T.; Koinis-Mitchell, Daphne; McQuaid, Elizabeth L.
Abstract: Background: Asthma disproportionately impacts youth from marginalized minority backgrounds. Aspects of core asthma management (asthma management and medication beliefs) were examined among a cohort of diverse families. Methods: Caregiver-youth dyads ( N  = 92; Mage = 13.8 years; non-Hispanic/Latinx White (NLW) = 40%; Black/African-American = 25%; Hispanic/Latinx= 35%) completed a medication beliefs questionnaire (Medication Necessity, Medication Concerns) and a semi-structured interview (Family Asthma Management System Scale (FAMSS)). FAMSS subscales (Asthma Knowledge, Symptom Assessment, Family Response to Symptoms, Child Response to Symptoms, Environmental Control, Medication Adherence, Family-Provider Collaboration, and Balanced Integration) were used for analyses. Results: More Hispanic/Latinx families were at or below the poverty line (75%) relative to NLW (22%) and Black/African-American (39%) families ( p  < 0.001). Adherence ( p  < 0.01), Knowledge ( p  < 0.001), and Symptom Assessment ( p  < 0.01) were higher for NLW relative to Black/African-American families. Collaboration was higher among NLW ( p  = 0.01) and Hispanic/Latinx families ( p  = 0.05). Effect sizes were moderate ( η 2 = 0.10–0.12). Parental race/ethnicity moderated the relationship between adherence and parental perceived medication concern and necessity for NLW and Hispanic/Latinx families. As medication concerns increased, medication adherence decreased, however, only for NLW and Hispanic/Latinx families. Conclusions: In this sample, racial/ethnic differences emerged for elements of asthma management. Interview-based ratings of asthma management among Black/African-American families depicted lower asthma knowledge, lower levels of family-provider collaboration, and lower medication adherence. The relationship between medication concerns and adherence appeared to differ by ethnic group. Future research is needed to elucidate cultural factors that influence family-provider relationships and health-related behaviors, like medication use/adherence.